Experience of applying a new European chondroprotector in patients with stage 1–2 osteoarthritis in general medical practice - T. N. Kargaeva (Лечащий Врач, 2021)
The effectiveness of the new European chondroprotector in combined therapy in the 1–2 stage of osteoarthritis (OA) of different localization was estimated. The study included 358 patients with knee and hip joint OA, as well as polyosteoartrosis. According to the study, all patients experienced a decrease in the severity of pain, a decrease in need for analgesics, an increase in functional activity and improvement in the quality of life. The drug is well tolerated, and patients demonstrated high adherence to treatment.